Categorizing social vulnerability patterns in Chinese coastal cities. (November 2015) - Su, Shiliang; Pi, Jianhua; Wan, Chen; Li, Huilei; Xiao, Rui; Li, Binbin
Abstract: Coastal cities play a leading role in world development; however, they are highly vulnerable to natural disasters given their specific locations and rapid urbanization pace. Characterizing the social vulnerability of coastal cities to hazards should provide critical references for coastal management. This paper developed a composite social vulnerability index (SVI) for Chinese coastal cities by integrating 17 indices from three aspects (exposure, sensitivity and adaptive capacity) that shaped the vulnerability of urban society to hazards; and then verified SVI effectiveness by quantifying its correlation with the total economic loss of hazards. Social vulnerability patterns along the Chinese coast in 2000, 2005 and 2010 were then obtained. Results showed that cities around the Bohai Bay generally presented lower SVI values in the three years. Cities in the eastern and southeastern coast generally had higher SVI values in space but became lower with time. Conversely, SVI values became higher for cities in Hainan and Guangxi Province. The clustering approach categorized the 53 cities into different groups according to their profiles of vulnerability. These categorized groups could facilitate more targeted coastal management options. This paper highlighted that adaption should be incorporated in analyzing the reaction of urban society to hazards. The SVI was believed to be an applicable and reliable tool to inform coastal management. Highlights: A composite index of social vulnerability was developed and proven to be effective. Social vulnerability of Chinese coastal cities were compared and categorized. Adaption should be incorporated in coping with hazards. Area-specific coastal management practices should be formulated.